Variation in detection limits between bacterial growth phases and precision of an ATP bioluminescence system. (1st April 2014) - Vogel, S.J.; Tank, M.; Goodyear, N.
Abstract: To determine the detection limits of the SystemSure Plus, Escherichia coli and Staphylococcus aureus growth curve samples were taken in lag (1 h), log (6 h), stationary (12 h) and death phases ( E. coli 144 h, Staph. aureus 72 h). At each time point, the log10 CFU ml −1 was determined for the dilution where the SystemSure read 0 relative light units (RLU). Average detection limits were E. coli : lag 6·27, log 5·88, stationary 7·45 and death 6·88; Staph. aureus : lag 4·37, log 5·15, stationary 7·88 and death 7·57. Between‐run precision was determined with positive control; within‐run precision with positive control, lag and log growth for each bacteria. Within‐run precision mean RLU (CV): positive control 274 (12%), E. coli lag 1 (63%), log 2173 RLU (19%), Staph. aureus lag 2 (58%) and log 5535 (18%). Between‐run precision was 232 (16%). The precision is adequate with most values within the 95% confidence interval. The detection limit varied by 3·51 log10 for Staph. aureus and 1·47 log10 for E. coli . The lowest detection limits were during E. coli log and Staph. aureus lag phases; the highest was during stationary phase. These results suggest that organism identification and growth phase both impact ATP RLU readings. Significance and Impact of the Study: Surface hygiene is a critical component of food safety and infection control; increasingly, ATP detection by bioluminescence is used to evaluate surface hygiene and effective cleaning. This is the first study to show that the number of living and potentially infectious bacteria remaining when the device reads zero varies between the different bacterial life cycle phases: lag, log, stationary and death. ATP device users need to be aware of this information to use the devices appropriately.